Effectiveness of Using LSE (Landslide Education) Mobile Digital Platform to Measure Knowledge of Senior High School Students - Sari, Alifa Ambar; Juhadi, Juhadi; Tjahjono, Heri; Setyowati, Dewi Liesnoor; Wijayanto, Pradika Adi (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2025)
Smartphone-based media that is increasingly sophisticated has the potential to be used in learning to be effective. This study aims to measure the effectiveness of the LSE (Landslide Education) application to increase knowledge about landslide disasters among high school students. This quantitative descriptive study uses a pre-experimental design with a one-shot case study model. The research subjects used a purposive sample of 141 students from grades XII F 7- XII F of SMA Negeri 12 Semarang. Data collection used post-test data test techniques, while non-test techniques were through observation, questionnaires, and documentation. Based on the results of the study, the average knowledge of the parameters of landslide disaster, knowledge of the distribution of landslide-prone areas in Semarang City, knowledge through education, local wisdom, and use of technology is 87. Hence, it is very good, while the average result of the student perception questionnaire using the LSE (Landslide Education) application is 83, so it is included in the good category. Based on these results, using the LSE (Landslide Education) application effectively increases Senior High School 12 Semarang disaster knowledge.